The Influence of Digital HR Practices on Employee Performance in E-Commerce MSMEs : The Role of Work Engagement as a Mediator and Digital Leadership as a Moderator - Tritisari, Angga; Eliyana Eliyana; Maria Christina Iman Kalis (LPPM STIE Kasih Bangsa, 2026)
The increasingly rapid digital transformation demands that MSMEs optimize technology not only in business processes but also in human resource management. Although HR digitalization is believed to improve organizational effectiveness, research on the psychological mechanisms and role of leadership in the context of e-commerce MSMEs is still limited. This study used a quantitative approach with an explanatory survey method and involved 366 respondents from e-commerce MSMEs in various regions of Indonesia. Data analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM) techniques to test direct relationships, mediation, and moderation. The results showed that digital HR practices have a positive and significant effect on employee performance. The digitalization of HR functions, such as e-recruitment, e-learning, HRIS, and digital performance management, can improve work effectiveness and the quality of work output. Furthermore, work engagement was shown to mediate this relationship, meaning that employees perform better when they feel more passionate, dedicated, and involved in their work. This mediating role emphasizes the importance of psychological aspects in the successful implementation of digital HR. Leaders who possess a digital vision, provide technological support, and encourage innovation have been shown to increase employee motivation and comfort in working using digital systems. Overall, this study confirms that the success of digital transformation in e-commerce MSMEs is determined not only by the technology used, but also by leadership support and employee engagement. These findings provide important contributions to the digital HR management literature and offer practical implications for MSME owners in increasing competitiveness in the digital era.